Perfil epidemiológico da hanseníase e sua relação com a Atenção Primária à Saúde em um município hiperendêmico do Mato Grosso - Souza, Márcio Henrique de (2021)
Leprosy is among the main infectious and contagious diseases, neglected and still considered a serious problem for public health. When diagnosed late, it increases the chances of neural injuries and transient and / or permanent physical disabilities, impacting the psychic and modifying social, professional and family life. In view of this scenario, Primary Health Care (PHC) presents itself as a proposal for disease control. The aim of this study was to analyze the relationship between leprosy and PHC's ability to coordinate Health Care Networks (RAS) in the municipality of Sinop, Mato Grosso. This was a cross-sectional study carried out in the municipality of Sinop, Mato Grosso and covering three analytical stages: characterization of the epidemiological profile of new leprosy cases; application of the instrument for assessing the coordination of RAS by PHC in Basic Health Units UBS; and correlation of the number of cases, types of discharge, the Degree of Physical Disability (GIF) at the time of diagnosis and treatment outcome with the PHC's ability to coordinate (RAS) and correlation between the number of new cases and the historical average of PHC coverage, using Pearson's correlation coefficient. The study considered the cases of leprosy notified between 2014 and 2018, the latter being the year with the highest percentage of notification. Of the 1,649 new cases reported, 63% were in women, people between 16 and 59 years old (83%), with up to 9 years of study (47%) and self-declared blacks (61%). Dimorfos accounted for 98% of notifications and main form of detection was through referrals and spontaneous demand with 33%, each. The UBS “Jacarandás” stood out with 16% of the registered cases and it was observed that in approximately 86% of the cases there was an exit due to cure and 9% due to abandonment. In the evaluation of the GIF, 58% were diagnosed with “GIF 0” in the diagnosis and 17% were not evaluated at the time of discharge. Regarding the PHC's ability to coordinate the RAS, it was noted that all participating BHUs were classified as ‘Good condition’. In the analysis of the correlation between PHC competence in conducting HCN and the dependent variables, the “Moderate correlation” and p-value of 0.03 stood out, the Type of Exit “abandonment” with r of -0.437. In the analysis between the historical average of coverage and the number of cases, a “very high” correlation with r of 0.96 and p-value of 0.04. We conclude that leprosy remains a public health problem and that actions need to be taken for this coping policy to evolve. The municipality has made progress in detecting the number of cases, but which aspects related to the management and monitoring of the patient need reflection and new strategies. The expansion of PHC is an important factor in the detection of new cases, but it is insufficient when worked in isolation. Making RAS effective by working with municipal priorities and strengthening PHC so that it conducts actions should be the way to face the disease.